Analiticidade e suavidade micro-local para soluções de equações diferenciais parciais não lineares de primeira ordem - Medrado, Renan Dantas (2012)
This work intends to study the analytic wave front set and theC8wave front set ofupx,0q, assu-ming that the partial differential equationsut fpx,t,u,uxqpresents a solutionu upx,tqPCk